Study of consumer attitudes towards insect-based foods utilising Q method & the exploration of insect protein gels formulation. - Iliopoulou, Viktoria (2020)
The food industry will have to take advantage of novel sustainable food ingredients to meet the needs of the growing world population whilst attempting to reduce malnutrition, and the environmental impact of food production. Of particular concern is the need to meet the demand for protein due to the environmental cost of livestock production, changing diets and in many countries an ageing population. One of the novel sources of sustainable proteins is insects, due to their high protein content and low environmental impact, although there is a lack of acceptance by consumers in developed countries.